2020
DOI: 10.1002/14651858.cd010215.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions for people with hemophilia

Abstract: Analysis 2.3. Comparison 2 Computerised learning compared to no intervention, Outcome 3 Coping strategies: selfmanagement ability and transition readiness (change from baseline

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…After the educational training, and despite the low margin for improvement, we observed an average of a 15% difference in the test score before and after the educational intervention. These results reinforce previous recommendations to act on the patients’ understanding and acceptability of their disease and treatment, as there is always room for improvement and enhancing quality of life [ 25 , 26 ]. Indeed, patients have high expectations for next-generation treatments, especially related to a reduced burden of administration, improved outcomes and more independence to live a “normal life” [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 87%
“…After the educational training, and despite the low margin for improvement, we observed an average of a 15% difference in the test score before and after the educational intervention. These results reinforce previous recommendations to act on the patients’ understanding and acceptability of their disease and treatment, as there is always room for improvement and enhancing quality of life [ 25 , 26 ]. Indeed, patients have high expectations for next-generation treatments, especially related to a reduced burden of administration, improved outcomes and more independence to live a “normal life” [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, individual variability and psychosocial factors are potential contributors to pain experience in patients, and the diverse methodologies employed in pain measurement amplify this variability, emphasising the need for careful consideration in research approaches. 56,57 The emergence of acute pain in a location not previously reported in the patient's medical history should be carefully considered during clinical evaluations, as it could potentially serve as a crucial factor for an emergent additional diagnosis in PWH. In this view, pain can be seen in its traditional physiological protective role, being a burdensome but 'good' signal that prevents the consequences of an untreated disease.…”
Section: Discussionmentioning
confidence: 99%
“…This points to the presence of additional variables influencing the diversity in pain perception, necessitating focused attention from the research community. Indeed, individual variability and psychosocial factors are potential contributors to pain experience in patients, and the diverse methodologies employed in pain measurement amplify this variability, emphasising the need for careful consideration in research approaches 56,57 …”
Section: Discussionmentioning
confidence: 99%
“…Few randomized controlled trials have been conducted focusing on psychology among bleeding disorder populations. A recent Cochrane review of only seven studies found limited evidence for the efficacy of psychological therapies to improve QOL in PwH 35 . Recent advancements in controlling bleeding could allow focus to shift towards exploration of complex psychological factors in improving QOL among PwBD.…”
Section: Discussionmentioning
confidence: 99%